Agrobiodiversity in home gardens and food and nutritional security of households in Monteverde, Costa Rica - Arias Ramírez, Jéssica (2024)
Agrobiodiversity is believed to be associated with a wider diversity of diets and a reduction in food and nutrition insecurity (FNI). Consequently, agrobiodiversity of home gardens and their potential impact on food and nutrition security (FNS) in households in San Luis, Monteverde, an area that previously experienced high levels of FNI, was researched. A total of 23 households with family gardens was assessed, and the persons responsible for the gardens were interviewed to gather information about their households and their gardens. Additionally, plant and animal species were identified and their uses in those spaces were reported. To measure household FNS, a scale focusing on the access component was applied. Results indicated that approximately 65.2% of households experienced some degree of FNI. Analyzing the possible correlation between agrobiodiversity and household FNS revealed a trend, households with more diverse home gardens tended to exhibit better FNS outcomes than home gardens with fewer species. These findings suggest that well-managed agrobiodiversity in family gardens can play a significant role in improving the FNS of rural families.